Injection practices of healthcare professionals in a Tertiary Care Hospital - H.S. Rehan; Deepti Chopra; Ravinder Kumar Sah; Tanuj Chawla; Arpit Agarwal; G.K. Sharma (Elsevier, 2012)
Background: Unsafe injection practices are prevalent worldwide and may result in spread of infection. Thus the present study was planned to observe the injection practices of healthcare professionals (HCP), including aseptic precautions and disposal of used syringes/needle. Materials and methods: Injection practices were observed in the outpatients and inpatients departments. Questionnaire was designed, tested and administered for this purpose. Results: 130 patients receiving injections were observed. Overall injection practices of the HCP were satisfactory. However, unsafe practices with respect to not washing hands (95.4%), not wearing/changing gloves (61.6%), recapping of needles (12.2%), wiping of needle with swab (15.4%) and breaking of ampoule with solid object (44.4%) were observed. Conclusion: The problem of unsafe injections can be successfully addressed by organizing continuing medical education/symposium/workshops for improving the knowledge, attitude and practices of the HCP. Periodic monitoring and such interventions may also further improve safe injection practices. Keywords: Injection practices, Unsafe injections, Disposal of used syringes/needle